PENGARUH PROFESIONALISME AUDITOR TERHADAP TINGKAT MATERIALITAS DALAM PEMERIKSAAN LAPORAN KEUANGAN - Rophinta Violyta; Lorina Siregar Sudjiman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
This study aims to see and determine the effect of Auditor Professionalism on the Materiality Level in the Examination of Financial Statements. the method used by the author is quantitative. With 52 auditors as a sample of 6 accounting firms. The technique used in this study is the multicollinearity test technique, autocorrelation test, standard probability plot test, T-test, and F test. The survey results reveal a significant effect of Auditor Professionalism on the Materiality Level in the Examination of Financial Statements.